Effect of dynamic cerebral autoregulation on the association between deep medullary vein changes and cerebral small vessel disease - He, Ling; Guo, Zhen-Ni; Qu, Yang; Wang, Run-Ting; Zhang, Peng; Yang, Yi; Jin, Hang (Frontiers in Physiology, 2023)
Changes in the deep medullary vein (DMV) are reported to be associated with cerebral small vessel disease (CSVD). While the mechanisms of this association are unclear, dynamic cerebral autoregulation (dCA) has been speculated to participate in this association. Thus, we aimed to verify the association between DMV changes and total CSVD burden and further investigate the effect of dCA function on this correlation. In this prospective study, 95 Asian patients aged ≥18 years were included in the final assessment. DMV scores and total CSVD burden were determined using magnetic resonance imaging sequences. Transfer function analysis was performed to analyze dCA function. Generalized linear regressions were used to assess the relationship between DMV changes and total CSVD burden as well as between DMV changes and dCA function. An interaction model was utilized to assess the effect of dCA function on the association between DMV changes and total CSVD burden. Generalized linear models showed a significant positive association between DMV changes and total CSVD burden (P=0.039) and a significant negative association between DMV changes and dCA function (P=0.018). The interaction model demonstrated a significant positive interaction of dCA impairment on the association between DMV changes and the total CSVD burden (P=0.02). Thus, we came to the conclusion that changes in DMV were correlated independently with both CSVD and dCA impairment and furthermore, impaired dCA function play an interaction effect on the association between DMV changes and the total CSVD burden. Our results can help improve the understanding of the complex pathogenesis and progression of CSVD, thereby facilitating early intervention and treatment development.